Study on the Lead and Lag Relationship Between the Kuala Lumpur Stock Exchange Composite Index Futures Contract and its Underlying Kuala Lumpur Stock Exchange Composite Index - Abdullah, Mahdhir (2001)
The birth of the Kuala Lumpur Stock Exchange Composite Index futures contract (FKLI) in December 1 995 creates a lot of opportunities for research in the area of financial derivatives. This paper looks into the lead and lag relationship between the FKLI returns and the Kuala Lumpur Stock Exchange Composite Index (KLSE CI) returns since the inception of the stock index futures trading in December 1 995 until December 2000. The five-year period is segmented into three subperiods to see the lead-lag behaviour under different market volatility levels. The three subperiods are: Subperiod 1 ) from inception to June 1 997, Subperiod 2) from July 1 997 to September 1 998, and Subperiod 3) from October 1 998 to December 2000. The first subperiod reflects the period of stable prices and thin futures trading volume, the second subperiod represents the period of highly volatile market and huge futures trading volume, and the third subperiod reflects the period of reasonably stable prices and fairly high trading volume. In this study, a multiple regression model is used as the methodology to test for the lead and lag relationship between the stock index futures returns and KLSE CI returns. The study finds that there is a strong contemporaneous relationship and there exists a lead effect from the futures market to the spot market by one day in subperiods 1 and 3 . Subperiod 2 shows a mix lead-lag relationship between the two markets. For the whole period under review, the relationship has been found to be ambiguous and inconclusive.